EXPLORING THE ANTIDIABETIC, LIPID-LOWERING, AND TISSUE REPAIR BENEFITS OF MULTI-COMPONENT MICROSPHERES IN STREPTOZOTOCIN-INDUCED DIABETIC RATS - ANUSHREE CHAUHAN,; SURBHI GUPTA,; PRABHAT SINGH,; PRASAD MISHRA , GANESH (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Dapagliflozin, linagliptin, and metformin are extensively utilized either alone or in combination to manage insulin-resistant diabetes. However, the precise administration and effectiveness of their triple combination through a microsphere formulation is yet to be thoroughly explored. This study sets out to explore the antidiabetic and hypolipidemic effects, as well as the histopathological impact of microspheres drug delivery system in streptozotocin (STZ)-administered diabetic rats. Methods: Following an overnight fast, both healthy and diabetic rats were separated into five sets each containing six rats, receiving daily oral treatments for 21 days. Group 1 (control) was administered saline (0.9% NaCl), Group 2 (STZ) received STZ (65 mg/kg through an intraperitoneal injection.), Group 3 (STZ and metformin) received metformin (150 mg/kg), Group 4 (STZ and empagliflozin + linagliptin + metformin) received a tablet combination of these drugs, and Group 5 (STZ and dapagliflozin+linagliptin+metformin) was treated with dapagliflozin (5 mg/kg), linagliptin (5 mg/kg), and metformin microspheres (150 mg/kg). Plasma glucose concentration was monitored weekly, and lipid functions were assessed after 21 days. Histopathological examinations of the pancreas and kidneys were also conducted. Results: The microsphere combination of dapagliflozin, linagliptin, and metformin significantly improved blood glucose levels (109.10±4.13 mg/dL), renal and hepatic functions, and showed beneficial effects on lipid parameters, particularly high-density lipoprotein levels (32.17±3.4 mg/dL), which could lower risk of cardiovascular diseases. Histopathological analysis revealed positive effects on the pancreas and kidneys. A p<0.05 was considered to indicate statistical significance. Conclusion: The microsphere formulation of the triple drug combination demonstrates synergistic antidiabetic properties, enhances body weight, improves lipid profiles, and supports renal and hepatic functions. In addition, it protects against tissue damage to the pancreas and kidneys in STZ-mediated experimental diabetes.